Community-Based Arts Education Management at U2 Java Dancer Studio: A Qualitative Case Study - Sesaria Prima Yudhaningtyas; Warih Handayaningrum; Welly Suryandoko; Setyo Yanuartuti; Indar Sabri (Jurnal Pendidikan Terapan, 2026)
Purpose: This study examines the management of community-based arts education at U2 Java Dancer Studio, focusing on curriculum implementation, mechanisms of Javanese cultural transmission, character and emotional intelligence development, and contributions to Sustainable Development Goal 4 (SDG 4). Methods: A qualitative single-case study design was employed. Data were collected over six months through participant observation, in-depth interviews with nine informants (studio leader, instructors, students, and parents), and document analysis. Data were analyzed inductively through coding, categorization, and thematic interpretation. Findings: The study found that U2 Java Dancer Studio applies a structured thematic rotation curriculum with classical Javanese dance serving as a foundational learning framework. Cultural transmission occurs through four interconnected mechanisms: intergenerational learning, embodied learning, contextualization of cultural meanings, and community performances. Dance education also promotes character development and emotional intelligence, particularly confidence, respect, patience, empathy, and aesthetic sensitivity. The studio contributes to SDG 4 by expanding access to inclusive non-formal arts education, supporting lifelong learning, preserving local cultural knowledge, and strengthening community participation in education. Research Implications: The findings highlight the strategic role of community-based art studios as non-formal educational institutions that integrate cultural preservation, character formation, and sustainable education. The study provides practical insights for policymakers and educators seeking to strengthen arts-based educational initiatives. Originality: This study offers an integrated perspective on arts education management, cultural transmission, emotional intelligence development, and sustainable education within a community-based dance studio context, extending the discourse on non-formal education in Indonesia.